2004
DOI: 10.3758/cabn.4.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating semantic and phonological maintenance using fMRI

Abstract: Functional magnetic resonance imaging (fMRI) distinguished regions of neural activity associated with active maintenance of semantic and phonological information. Subjects saw a single word for 2 sec, and following a 10-sec delay, made a judgment about that word. In the semantic task, subjects focused on the meaning of the word and decided whether a second word was synonymous with it. In the phonological task, subjects repeated the word silently and decided whether it shared a vowel sound with a nonsense word.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 45 publications
9
60
3
Order By: Relevance
“…Consistent with previous studies reporting activation in response to phonological tasks with heard and written words [Burton et al, 2003;Devlin et al, 2003;Fujimaki et al, 1999;Gold et al, 2005;Gold and Buckner, 2002;McDermott et al, 2003;Mummery et al, 1998;Poldrack et al, 1999;Price et al, 1997;Roskies et al, 2001;Shivde and Thompson-Schill, 2004], phonological decisions on pictures of objects (relative to semantic, perceptual, and resting conditions) activated bilateral inferior frontal, insula, precentral, and posterior lateral inferior temporal cortices, supramarginal gyri, ante-rior cingulate, supplementary motor area (SMA), cerebellum, and the left thalamus (Table IV). Critically, these phonological activations included 6 of 12 areas that were more activated in the object-naming meta-analysis for low Ͼ high baselines (all in the left hemisphere): frontal operculum (fo); inferior frontal (if-t); cerebellum (cb), insula (in); thalamus (th); and cingulate gyrus (cg).…”
Section: Phonological Activationsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies reporting activation in response to phonological tasks with heard and written words [Burton et al, 2003;Devlin et al, 2003;Fujimaki et al, 1999;Gold et al, 2005;Gold and Buckner, 2002;McDermott et al, 2003;Mummery et al, 1998;Poldrack et al, 1999;Price et al, 1997;Roskies et al, 2001;Shivde and Thompson-Schill, 2004], phonological decisions on pictures of objects (relative to semantic, perceptual, and resting conditions) activated bilateral inferior frontal, insula, precentral, and posterior lateral inferior temporal cortices, supramarginal gyri, ante-rior cingulate, supplementary motor area (SMA), cerebellum, and the left thalamus (Table IV). Critically, these phonological activations included 6 of 12 areas that were more activated in the object-naming meta-analysis for low Ͼ high baselines (all in the left hemisphere): frontal operculum (fo); inferior frontal (if-t); cerebellum (cb), insula (in); thalamus (th); and cingulate gyrus (cg).…”
Section: Phonological Activationsupporting
confidence: 89%
“…To our knowledge, no previous study has reported such a comparison, even though there are numerous functional imaging reports that have compared semantic and phonological tasks when the stimuli are written words [Burton et al, 2003;Devlin et al, 2003;Fujimaki et al, 1999;Gold et al, 2005;Gold and Buckner, 2002;McDermott et al, 2003;Mummery et al, 1998;Poldrack et al, 1999;Price et al, 1997;Roskies et al, 2001;Shivde and Thompson-Schill, 2004]. These previous studies of written word processing have shown consistently that activation is enhanced for phonological relative to semantic decisions in posterior inferior frontal and supramarginal gyri (BA40), and semantic relative to phonological decisions in anterior inferior frontal, the angular gyrus, and posterior and middle temporal areas.…”
Section: Figurementioning
confidence: 98%
“…There is a distinction in this region between anterior and posterior areas of this region, which seem to be relatively specialized for either semantic (the anterior part (BA 45/47/10)) or phonological (posterior regions (BA 44/6)) processing. The posterior regions of the brain activated in these tasks seem to have a relatively greater involvement in retrieval of stored information such as word meaning (BA21) (Demb et al, 1995;McDermott et al, 2003;Poldrack et al, 1999;Shivde & Thompson-Schill, 2004) or sound (BA7/40) (McDermott et al, 2003;Shivde & Thompson-Schill, 2004). Therefore, the findings on our activation maps correlate with the general knowledge about the distribution of the semantic and phonological networks in the brain (Crosson et al, 2003;Devlin et al, 2003;McDermott et al, 2003;Poldrack et al, 1999;Thompson-Schill et al, 1997).…”
Section: Discussionsupporting
confidence: 70%
“…The inferior frontal region, including the insula and inferior frontal gyrus, activates when subjects are asked to remember and make decisions about both words and nonmeaningful phonological stimuli (Chee et al, 2004;Dehaene-Lambertz et al, 2005;Gelfand and Bookheimer, 2003;Jacquemot et al, 2003;LoCasto et al, 2004;Seghier et al, 2004;Shivde and Thompson-Schill, 2004). Similar to activation in the left temporal region, we might also expect less effort devoted to phonological maintenance would be associated with familiar words, resulting in a negative correlation with the task performance.…”
Section: Phonological Processesmentioning
confidence: 99%